Seleno-polymannuronate attenuates neuroinflammation by suppressing microglial and astrocytic activation - Decheng Bi; Qiuxian Lai; Qingguo Han; Nan Cai; Hanxing He; Weishan Fang; Jiang Yi; Xiaofan Li; Hong Xu; Xiuting Li; Zhangli Hu; Qiong Liu; et al. (Journal of Functional Foods, 2018)
Polymannuronate (PM) is an acidic polymer separated from alginate. PM is a linear block polysaccharide in edible brown algae that has been widely used in the food industry. Seleno-polymannuronate (Se-PM) is a seleno-derivative of PM synthesized from PM and Na2SO3 in our laboratory. We investigated the anti-neuroinflammatory activity of Se-PM in lipopolysaccharide (LPS)-activated primary microglia and astrocytes and a mouse model of acute inflammation. Our results show that Se-PM could markedly reduce NO and PGE2 production, iNOS and COX-2 expression, and TNF-α, IL-1β and IL-6 secretion in LPS-treated primary microglia and astrocytes. Moreover, the LPS-triggered overactivation of NF-κB and MAPK signalling was attenuated by Se-PM. In addition, in vivo, LPS-induced microglial and astrocytic activation was remarkably suppressed by Se-PM. These results suggest that Se-PM merits exploration as an alternative medicinal or functional food for alleviating neuroinflammation.